Highly concentrated iron ore slurry flow through pipeline with and without chemical additive; part II: 3d cfd modelling - Mishra Stuti; Kaushal Deo Raj (Journal of Hydrology and Hydromechanics)
This study involves a computational analysis of the flow of iron ore (with a mean particle diameter of 55 microns) slurry flow through a pipeline of 2-inch diameter. The analysis covers a flow velocity range of 1 to 3.5 m/s at high concentrations ranging from 60 to 72 % w/w without and with additive (Sodium-hexametaphosphate) at different dosages from 0.1 to 1.5% w/w of solids. A three-dimensional Computational Fluid Dynamics (3D CFD) model is developed and validated using experimental data collected in our previous studies (Part I). The Eulerian multiphase model is used with K-epsilon turbulence settings to simulate the flow. Based on comparison with experimental data, it is observed that the 3D CFD model can predict the pressure drop with an error band of ±30%. However, the 3D CFD model predicts the pressure drop very accurately for the velocity range of 2 to 3m/s for the entire range of solids concentrations considered in the present study. Distributions of concentration, velocity, and slip velocity along with granular pressure and granular viscosity are also computed and presented using the 3D CFD model developed in the present study for the entire ranges of solids concentration and flow velocity covered in the present study.